Mid-infrared emissivity of partially dehydrated asteroid (162173) Ryugu shows strong signs of aqueous alteration - Hamm, Maximilian; Grott, M.; Senshu, H.; Knollenberg, J.; Wiljes, Jana de; Hamilton, V. E.; Scholten, F.; Matz, K. D.; Bates, H.; Maturilli, A.; Shimaki, Y.; Sakatani, N.; et al. (Nature Communications, 2022)
The near-Earth asteroid (162173) Ryugu, the target of Hayabusa2 space mission, was observed via both orbiter and the lander instruments. The infrared radiometer on the MASCOT lander (MARA) is the only instrument providing spectrally resolved mid-infrared (MIR) data, which is crucial for establishing a link between the asteroid material and meteorites found on Earth. Earlier studies revealed that the single boulder investigated by the lander belongs to the most common type found on Ryugu. Here we show the spectral variation of Ryugu’s emissivity using the complete set of in-situ MIR data and compare it to those of various carbonaceous chondritic meteorites, revealing similarities to the most aqueously altered ones, as well as to asteroid (101955) Bennu. The results show that Ryugu experienced strong aqueous alteration prior to any dehydration.
Gesehen am 20.12.2022